Assessing changes in the mangrove ecosystem land area of Tanakeke Island, Takalar Regency, using Landsat 8 imagery - Dwi Rosalina; Katarina Hesty Rombe; Yasser Arafat; Khairul Jamil; Hawati Hawati; Anisa Aulia Sabilah; Warni Warni; Ani Leilani; Rezza Ruzuqi; Suci Puspita Sari; Eva Utami (Depik, 2024)
Rewataya Village is situated on Tanakeke Island, within the Takalar Regency. Despite its significance, previous studies have not addressed the mapping of changes in mangrove land area within this locale. The present research aimed to fill this gap by assessing alterations in mangrove land area from 2013 to 2023, alongside examining density and canopy cover conditions. The method employed for mapping changes in land area entailed utilizing the unsupervised method with maximum likelihood classification. Additionally, the assessment of mangrove conditions involved employing plot line transects to determine species density and hemispherical photography methods to evaluate canopy cover. Notably, two types of mangroves, namely Rhizophora mucronata and Rhizophora apiculata, are prevalent in this village. The mangrove species density in Rewataya Village, Tanakeke Island, is categorized as good. In addition, the canopy cover in Rewataya Village falls within the classification of very dense according to mangrove damage criteria. However, there has been a notable reduction in the mangrove ecosystem area between 2013 and 2023, with a decrease of 42.28 hectares (from 367.13 hectares to 324.84 hectares).Keywords: MangroveLandsat 8Rewataya villageUnsupervised